TINJAUAN KONSTITUSIONAL KEUANGAN NEGARA DALAM KEPAILITAN BADAN USAHA MILIK NEGARA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 43 PK/PDT.SUS-PAILIT/2019) - Benny Andreas Sinaga; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2022)
This study discusses the constitutional review of state finances in the bankruptcy of State-OwnedEnterprises through the case study of the Supreme Court Decision Number 43PK/PDT.SUS-PAILIT/2019 relating to the review of the bankruptcy of PT Kertas Leces. In Bankruptcythere are special provisions relating to the bankruptcy of State-Owned Enterprises, namely if aState-Owned Enterprise is engaged in the field of public interest, the Minister of Finance can only suefor bankruptcy. Meanwhile, for State-Owned Enterprises that operate privately or in the form of aLimited Liability Company, the creditors can go bankrupt. Bankruptcy in the State-Owned Enterprisesthen gave birth to problems in the perspective of state finances. State financial status in State-OwnedEnterprises is a separate state finance. However, there is an antinomy of meaning between the 1945Constitution and the State Finance Law, so that one and the other are contradictory. This study foundthat there is a dif erence in meaning between the meaning of separated state finances in the 1945Constitution and the State Finance Law which lies in the extent of the meaning of separated statefinances. However, based on the development of practice and the opinion of experts, the meaning ofseparated state finances is a broad meaning as regulated In the Law on State Finances, it was furtherdiscovered that the state cannot be bankrupt because the state assets in BUMN are assets that havebeen separated.